Efek Learning Management System Berbasis Google Classroom dan Minat Belajar Terhadap Hasil Belajar Ekonomi Siswa - Yulfianti, Septenti Yuti; Dewi, Retno Mustika (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The study aims to analyze the effect of google classroom based Learning Management System (LMS) and interest in learning on student learning outcomes. The type of this research is quantitative research with descriptive statistical methods. Research subjects were senior high school 3 Sidoarjo 10 social class , totaling 75 respondents. The instrument used in this study was a questionnaire used to measure the variable google classroom (X1) and interest in learning (X2). On the learning outcomes (Y) variable measured by the odd semester grade senior high school 3 Sidoarjo 10 social class. The data analysis technique used multiple linear regression analysis. The results of the study indicate that1)Â  There is an effect of Learning Management System based of google classroom on students economic learning outcomes 2) There is an influence of interest in learning on student learning outcomes and 3) There is the influence of Learning Management System based google classroom and interest in learning on student learning outcomes. The conclusion of this study is that The Learning Management System based on Google Classroom simultaneously affect learning outcomes.